Nutritional Evaluation of Energy Feed Sources for Ruminant Using In Vitro Gas Production Technique - Songsak Chumpawadee; Kritapon Sommart; Thevin Vongpralub; Virote Pattarajinda (Agriculture and Natural Resources, 2006)
Five energy feed sources were used to evaluate for nutritive value using the in vitro gas production technique. The rumen mixed microbe inoculums were taken from fistulated Brahman-Thai native crossbred steers. The energy feed source treatments were 1) corn meal, 2) cassava chip, 3) broken rice, 4) rice bran and 5) rice pollard. The treatments were assigned to completely randomize design (four replications). The results indicated that soluble gas fractions (a) (-32.39, -50.98, -34.02, -21.67 and -3.39 mL, respectively), the fermentation of the insoluble fraction (b) (132.39, 150.98, 134.02, 119.09 and 62.66 mL, respectively), rate of gas production (c) (0.12, 0.19, 0.08, 0.11 and 0.06 %/h , respectively) and potential of extent of gas production (a+b) (164.79, 201.97, 168.05, 140.76 and 66.05 mL, respectively) were significantly different (P<0.01) among energy feed sources. The cumulative gas volumes at 24, 48 and 96 h after incubation were significantly different (P<0.01). Cassava chip exhibited the greatest gas production characteristics and gas volume. These results together with its locally available at an inexpensive cost cassava chip was one of the potential energy source for beef and dairy cattle.